Studies on the High-Power Piezoelectric Property Measurement Methods and Decoupling the Power and Temperature Effects on PZT-5H - Wenchao Xue; Xiaobo Wang; Yuliang Zhu; Chengtao Luo (Sensors)
For those piezoelectric materials that operate under high-power conditions, the piezoelectric and dielectric properties obtained under small signal conditions cannot be directly applied to high-power transducers. There are three mainstream high-power characterization methods: the constant voltage method, the constant current method, and the transient method. In this study, we developed and verified a combined impedance method that integrated the advantages of the constant voltage and current methods, along with an improved transient method, for high-power testing of PZT-5H piezoelectric ceramics. The results from both methods indicated that with increasing power, the electromechanical coupling coefficient <semantics>k31</semantics> , the piezoelectric constant <semantics>d31</semantics>, and the elastic compliance <semantics><msubsup>s11E</msubsup></semantics> of the PZT-5H showed increasing trends, while the mechanical quality factor <semantics>Qm</semantics> first decayed rapidly and then stabilized at a fixed level. Additionally, under the combined impedance method, the temperature of the vibrators rose significantly due to self-heating, whereas the transient method generated almost no heat, and the vibrators remained at room temperature. By comparing the results from the two methods, we decoupled the effects of temperature and power on the high-power piezoelectric performance. The results showed that the self-heating temperature amplified the effects of power on <semantics>k31</semantics>, <semantics>d31</semantics>, and <semantics><msubsup>s11E</msubsup></semantics>, while its influence on <semantics>Qm</semantics> remained negligible.